The returner [compact disc] - Russell, Allison (Fantasy, 2023)
A record of fierce joy, The Returner is the new album from four-time Grammy-nominated singer, songwriter, and multi-instrumentalist Allison Russell. Co-produced by Allison along with dim star (JT Nero and Drew Lindsay), it features her "Rainbow Coalition" band of female musicians along with special guests: the legendary Wendy & Lisa, Brandi Carlile, Brandy Clark and Hozier. The follow-up to her acclaimed debut Outside Child, The Returner is a soulful expression of liberation, love, and self-respect.